Encyclopedia of aquaculture - Stickney, Robert R. (New York : Wiley, 2000)
"The encyclopedia looks at all forms of life, from nematodes to human beings, in 313 signed articles. The set covers a wide range of scientific and social science issues, making it a useful resource for learning about purely scientific concepts as well as issues concerning human effects on the environment. Academic and larger public libraries will find this work invaluable for answering questions about environmental and biological topics."--"Outstanding Reference Sources," American Libraries, May 2001.
Includes bibliographical references and index.
Keywords: Aquaculture -- Encyclopedias